Settlement Patterns and Fortification Architecture in the Central Highlands of Yemen. (14th January 2019) - Mahoney, Daniel
Abstract : Located in the central highlands of Yemen at approximately 2, 000-2, 600 meters above sea level, the Dhamar Plain was the home of a tribal population who continually contended with a succession of invading states for its control over the course of medieval and early modern periods, such as the Rasulids (13th-14th cen.) and the Ottomans (16th-17th cen.). Despite the roughly century-long duration of theses occupations, only minimal physical remains are left of their military architecture in contrast to the abundance of local fortified structures still remaining. This article examines their settlement patterns and types of fortification as based on survey results from the Dhamar Survey Project (DSP) and the Dhamar Museum Survey (DHS). Emerging from a strong vernacular tradition that extends back to the prehistoric period, these architectural forms range from singular tower houses and watchtowers to more extensive citadels and walled settlements. Overall, this diversity indicates well-developed schemes that aim to maximize both arable land for agriculture and the safety of the inhabitants on both a household and community level.